Sterilization of ready to serve product for special needs of Hajj and Umrah: Skipjack tuna in a retort pouch package - Azhari, Elsa; Aliredjo, Muhamad Subroto; Purnomo, Agus Heri; Damat, Damat; Mel, Maizirwan; Wahono, Satriyo Krido; Suherman, Suherman; Yandri, Erkata (EDP Sciences, 2023)
One crucial period in the provision of food for Hajj/Umrah is the time between opening the package and consuming it by the pilgrims. This study aimed to determine the sterilization time to prevent damage and maintain acceptance by consumers. The methodology of this research was sterilization with variations in retort pressure settings and raw materials: (A) 1.8 bar pressure, 100 % skipjack; (B) 1.2 bar pressure, 90 % skipjack; (C) 1.2 bar pressure, 70 % skipjack; (D) 1.8 bar pressure, 50 % skipjack. The analysis included two components. The (i) was the determination of the adequacy of sterilization time, the (ii) was the observation of quality deterioration, which was based on organoleptic and Total Plate Count. The results showed that the adequacy of sterilization for variations A, B, C, and D was: 121.5 °C for 4.8 min; 114.5 °C for 4.8 min; 115.4 °C for 5.31 min, and 124.0 °C for 13.4 min. TPC analysis, which was carried out at 0 h, 3 h, 9 h, and 12 h in a row were 4 × 100 , 2 × 102 , 2 × 102 , and 3 × 103 . In terms of consumer acceptance, sterilized products have good values, with organoleptic values ranging from 7.8 to 8.2 (scale 1 to 10)